Effects of qualification in expert markets with price competition and endogenous verifiability - Tim Schneider; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
We investigate a market in which experts have a moral hazard problem because they need to invest in costly but unobservable effort to identify consumer problems. Experts have either high or low qualification and can invest either high or low effort in their diagnosis. High skilled experts are able to identify problems with some probability even with low effort while low skilled experts here always give false recommendations. Experts compete for consumers by setting prices for diagnosis and service. Consumers can visit multiple experts, which enables an endogenous verifiability of diagnosis. We show that with a sufficient number of high skilled experts, stable second-best and perfectly non-degenerate equilibria are possible even with flexible prices, although they depend on transactions costs being relatively low. By contrast, with a small share of high skilled experts in the market, setting fixed prices can be beneficial for society.
Keywords: L10; D82; D40; 330; credence goods; expert market; moral hazard; qualification; competition; second opinions; diagnostic effort